Erin Brockovich - DeVito, Danny; Shamberg, Michael; Sher, Stacey; Grant, Susannah; Soderbergh, Steven; Universal Pictures (Firm); Colombia Pictures; Jersey Films; Universal Studio Home Video (Firm) (Universal City, CA : Universal Studio Home Video, 2000)
Julia Roberts stars as Erin Brockovich, a fiesty young mother who fought for justice any way she knew how. Desperate for a job to support herself and her three children, she convinces attorney Ed Masry (Albert Finney) to hire her, and promptly stumbles upon a monumental law case against a giant corporation. Now, Erin's determined to take on this powerful adversary even though no law firm has dared to do it before. And while Ed doesn't want anything to do with case, Erin won't take'no' for an answer. So the two begin an incredible and sometimes hilarious fight that will bring a small town to its feet and a huge company to its knee.
Based on a true story
Photographed by, Ed Lachmen ; edited by, Anne V. Coates ; music, Thomas Newman
Cast : Julia Roberts, Albert Finney, Aaron Eckhart
Keywords: Liability for water pollution damages -- California -- Drama; Drinking water -- Contamination -- California -- Drama